2005
DOI: 10.1128/iai.73.11.7274-7280.2005
|View full text |Cite
|
Sign up to set email alerts
|

Partially Assembled K99 Fimbriae Are Required for Protection

Abstract: Antibodies to K99 fimbriae afford protection to F5؉ bovine enterotoxigenic Escherichia coli (ETEC). Previous studies show that murine dams immunized with Salmonella vaccine vectors stably expressing K99 fimbriae confer protection to ETEC-challenged neonatal pups. To begin to address adaptation of the K99 scaffold to display heterologous B-and T-cell epitopes, studies were conducted to determine how much of the assembled K99 fimbria is required to maintain protective immunity. Sequential deletions in the K99 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…It was originally hypothesized that altering the expression of the CfaB fimbrial subunit could impact the types of Th cells induced, as previously observed in altering FanC expression for K99 fimbriae by Salmonella (23). While the induced Th cells were altered, as described here with the AP331 strain, protection against EAE was still maintained.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was originally hypothesized that altering the expression of the CfaB fimbrial subunit could impact the types of Th cells induced, as previously observed in altering FanC expression for K99 fimbriae by Salmonella (23). While the induced Th cells were altered, as described here with the AP331 strain, protection against EAE was still maintained.…”
Section: Discussionmentioning
confidence: 94%
“…AP331 was cultured in LB medium, as described above, and bacteria were harvested by centrifugation. Subcellular fractionation was performed according to manufacturer’s directions using the PeriPreps Periplasting Kit (Epicentre, Madison, WI), as previously described (22, 23). The different subcellular components were subjected to 15% SDS-PAGE and subsequently transferred to a nitrocellulose membrane for Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, recent data has shown that the use of a single fimbrial subunit from F4, the fimbrial adhesin subunit FaeG, does not provide good protection unless it is found in the polymerized fimbrial structure (232). Likewise, it has been shown that F5 needs to be assembled to induce immunity (519). Thus it is likely that vaccines for food animals produced using technologies that focus only on fimbrial subunits as immunogens will not result in good protection compared to polymerized, mature fimbrial strands.…”
Section: Vaccines and Colonization Inhibitorsmentioning
confidence: 99%
“…Our study revealed that the vaccination with E. coli vaccines protected mice against challenge with intraperitonially rout, this incompatible with study of Acres, et al [24] and Isaacson, et al [25], they found that the Purified pilus vaccines protect against challenge with ETEC strains that produce the same pilus antigen, and there are two lines of evidence that K99+ vaccines protect against challenge with ETEC strains that produce both K99 and F41 (K99+ F41+). A study of Asco`n, et al [26] showed that retention of K99 fimbrial subunit as native fimbriae or with the deletion of fanGH is sufficient to confer protection.…”
Section: Discussionmentioning
confidence: 99%